2017
DOI: 10.4236/ijohns.2017.66010
|View full text |Cite
|
Sign up to set email alerts
|

The Common Complications after Septoplasty and Septorhinoplasty: A Report in a Series of 127 Cases

Abstract: Background: There are many complications associated with septoplasty, which chiefly depend on the procedure performed. The aim of this study was to find out the common complications after Septoplasty and Septorhinoplasty in a series of 127 Saudi patients undergoing Septoplasty or Septorhinoplasty in Northern Saudi Arabia. Methodology: This study included a series of 127 patients presented with nasal blockage and subsequently undergone Septoplasty and /or Septorhinoplasty. Results: Complications were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…Once the risk factors have been identified, mistakes should be avoided. If there are no indications of mistakes in patient selection, preoperative planning, or operational technique, unsatisfactory outcomes can be attributed to complications [ 21 , 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…Once the risk factors have been identified, mistakes should be avoided. If there are no indications of mistakes in patient selection, preoperative planning, or operational technique, unsatisfactory outcomes can be attributed to complications [ 21 , 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…Most studies showed that objective measures to quantify and determine surgical success in the treatment of nasal obstruction do not correlate with subjective improvement as reported by patients. 3 The use of subjective ordinal scale to measure partitioning of airflow greatly increased the specificity of patient selection and it is proposed that these scales may be useful to the surgeon when assessing patients for septal surgery. 4 Sino nasal outcome test (SNOT) is a subjective tool, of one of its kind, in which both nasal and health-related symptomatic improvements are assessed.…”
Section: Introductionmentioning
confidence: 99%
“…5 Septoplasti, deviye septumu onarmak ve solunumu iyileştirmek için uygulanan en yaygın diğer önemli kulak-burun-boğaz ameliyatlardan birisidir. 6 Septorinoplasti ise rinoplasti ve septoplastiyi birleştiren patolojik, fizyolojik ve estetik sorunlar nedeniyle burnun sağ ve solunu ayıran nazal septuma yapılan karmaşık ikili bir cerrahi girişimdir. 8,9 Bu nedenle septorinoplasti, hem burnun şeklini değiştirmek hem de burundan soluk alıp vermeyi engelleyen septumu onarmak için yapılmaktadır.…”
unclassified
“…10,11 Septorinoplasti sonrası bazı estetik ve fonksiyonel komplikasyonlar ortaya çıkabilmektedir: Kanama, hematom, enfeksiyon, uzamış ödem, deformite ve burun havayolu tıkanıklığı burun ve gözlerde morarma, delinmiş bir septum, sinir hasarı, koku duyusunda azalma ve nadir olarak rinore. 4,6,7 Bu nedenle septorinoplasti ameliyatında beklenen estetik ve işlevsel hedefler, hastaların cerrahi gi-rişimiyle ilişkili kaygısını artırabilir. Hastaların ameliyat öncesi kaygı düzeyinin yüksek olması, ameliyat sonrası daha fazla ağrı ve memnuniyetsizlik gibi sorunlar yaşamasına neden olabilir.…”
unclassified